Julius Caesar - Shakespeare, William, 1564-1616.; Durband, Alan. (Woodbury, N.Y. : Barron$1 (Bs,s, 1985)
Presents the original text of Shakespeare$1 (Bs play side by side with a modern version, discusses the author and the theater of his time, and provides quizzes and other study activities.s
Keywords: Caesar, Julius -- Assassination -- Drama; Shakespeare, William, -- 1564-1616 -- Outlines, syllabi, etc; Caesar, Julius -- Drama; Shakespeare, William, -- 1564-1616.; Conspiracies -- Drama; Assassins -- Drama; Plays; Rome -- Drama